OP06. Genomic analysis of paired primary and recurrent glioblastoma samples - Stead, Dr Lucy (Neuro Oncol, 2017)
Primary glioblastoma (GBM) tumours recur following treatment. This is likely due to intratumour heterogeneity (ITH), which reduces the effectiveness of cancer therapies by enabling therapy-driven tumour evolution: Darwinian selection of genotypically and/or phenotypically distinct cells (subclones) that resist treatment to seed regrowth of an even less treatable recurrence. In recent years, next generation sequencing approaches have facilitated the characterisation of subclonal genomic tumour architecture. We have applied these approaches to a pilot cohort of five paired primary and locally recurrent GBM tumours, alongside high-coverage transcriptomic profiling, in order to begin characterising therapy resistant cells and thereby infer the mechanisms by which they evaded treatment. This approach may also indicate relevant targets in recurrent disease. In this preliminary cohort we see subclonal mutation patterns indicative of neutral tumour evolution but with evidence of selection of certain cell populations during therapy. The expressed, mutated genes in these expanded cell populations are enriched for EGF-EGFR signalling pathways and Wnt signalling and pluripotency, with at least one member of each of these pathways being mutated in an expanded subpopulation per tumour pair.